2020
DOI: 10.48550/arxiv.2001.04851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applications of Nijenhuis geometry: Nondegenerate singular points of Poisson-Nijenhuis structures

Alexey V. Bolsinov,
Andrey Yu. Konyaev,
Vladimir S. Matveev

Abstract: We study and completely describe pairs of compatible Poisson structures near singular points of the recursion operator satisfying natural non-degeneracy condition.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…This is again a question on gl-regular Nijenhuis operators. It is amazing that the answer turns out to be very similar to that given by Arnold: there is a very simple generic Nijenhuis perturbation of a Jordan block (see formula (6) and Proposition 5.1), which is unique and coincides exactly with the one given in [2]. All the others can be derived from this canonical one by solving a system of integrable PDEs.…”
Section: Outlook and Motivationmentioning
confidence: 53%
See 3 more Smart Citations
“…This is again a question on gl-regular Nijenhuis operators. It is amazing that the answer turns out to be very similar to that given by Arnold: there is a very simple generic Nijenhuis perturbation of a Jordan block (see formula (6) and Proposition 5.1), which is unique and coincides exactly with the one given in [2]. All the others can be derived from this canonical one by solving a system of integrable PDEs.…”
Section: Outlook and Motivationmentioning
confidence: 53%
“…A research programme and general strategy for studying such operators were suggested in [5]. This paper is devoted to the next item of our agenda (after [5], [6], [15]) and is focused on Nijenhuis operators satisfying gl-regularity condition.…”
Section: Basic Definitions and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper continues the Nijenhuis Geometry programme started in [1] and further developed in [2,3,20]. This programme was initially motivated by the fact that Niejnhuis operators (i.e.…”
Section: Introductionmentioning
confidence: 88%